1981
DOI: 10.1159/000115238
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cerebral Metabolism by Lidocaine

Abstract: The effects of lidocaine in high doses, i.e. higher than seizure doses, on cerebral function and metabolism are reviewed. Evidence is presented that lidocaine (160 mg/kg) reduces membrane Na+-K+ permeability, restricts leak fluxes of these ions, and decreases the load on the associated ion transport. In the ischemic brain (circulatory arrest in dogs on cardiopulmonary bypass circulation), lidocaine delays K+ efflux, indicating reduced membrane permeability. In the nonischemic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 5 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…The first fast voltage decay phase induced by ischemia and lasting about 8 min is probably an expression of ATP rollout and the consequent reduced Na/K-ATPase activity leading to an increase in the intracellular concentration of Na + and Ca 2+ [14,15] . The strong anti-edema effect of lidocaine reported here, more intense for the first 8 min of ischemia, can be a product of several processes beginning on the blocking action on voltage-activated sodium and potassium channels [4][5][6] , which produces a selective inhibition of Na + cellular influx and a subsequent reduction of Ca 2+ influx due to decreased membrane depolarization [24] together with reduced mitochondrial Na/Ca-ATPase activity, glucose and oxygen consumption [8,[24][25][26][27] . These reported ionic and membrane events could be the explanation to the strong increase in the time constant for voltage decay induced by lidocaine.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The first fast voltage decay phase induced by ischemia and lasting about 8 min is probably an expression of ATP rollout and the consequent reduced Na/K-ATPase activity leading to an increase in the intracellular concentration of Na + and Ca 2+ [14,15] . The strong anti-edema effect of lidocaine reported here, more intense for the first 8 min of ischemia, can be a product of several processes beginning on the blocking action on voltage-activated sodium and potassium channels [4][5][6] , which produces a selective inhibition of Na + cellular influx and a subsequent reduction of Ca 2+ influx due to decreased membrane depolarization [24] together with reduced mitochondrial Na/Ca-ATPase activity, glucose and oxygen consumption [8,[24][25][26][27] . These reported ionic and membrane events could be the explanation to the strong increase in the time constant for voltage decay induced by lidocaine.…”
Section: Discussionmentioning
confidence: 84%
“…Lidocaine, a well-known drug used as a local anesthetic [1] , heart antiarrhythmic [2] and antiepileptic drug [3] , produces a presynaptic block by reducing Na + inflow to the cell and K + outflow by means of the blockade of Na/K channels [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…The effect of reducing ion leak fluxes is also seen in hypothermia but not in thiopental, indicating lidocaine, not thiopental, has a membrane-sealing effect. [13] This membrane sealing effect (membrane stabilization) is related to energy to maintain cellular integrity that accounts for 40% of brain metabolism. 19 In this experiment, Astrup et al also measured the effect of lidocaine on CMRO 2 and cerebral metabolic rate for glucose (CMRgluc) by the sagittal sinus outflow method that allows continuous measurement of oxygen and glucose consumption.…”
Section: Discussionmentioning
confidence: 99%
“…In mammal experiments done by Astrup et al, lidocaine infusion resulting in flat electroencephalogram concluded that spontaneous electrocortical activity is abolished by lidocaine, similar to barbiturate action. [13,14] The abolition of electrocortical activity reduces 60% of energy consumption or brain metabolism. [19] In addition, lidocaine also affects Na-K leak fluxes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation